Finite Element Analysis of Strain Non-Uniformity in Two Processes of Severe Plastic Deformation - J. MACIEJEWSKI; H. KOPEĆ; H. PETRYK (Engineering Transactions, 2014)
Two severe plastic deformation (SPD) processing techniques, namely equal-channel angular pressing (ECAP) and cyclic extrusion-compression (CEC), are investigated by using the finite element method. The major aspect examined is the non-uniformity of the accumulated, equivalent plastic strain after processing with the use of different shapes of the die. The quantitative effect of several parameters on the plastic flow is determined. It is found that the diameter ratio of the chambers and narrower channel in the CEC method, and also the inclination angle of connecting conical parts, can affect strongly the degree of strain non-uniformity. Comparison is made of distributions of equivalent strain after two passes of ECAP for two different routes and with two die profiles.